Cloning, characterization and functional analysis of lichenase produced by Bacillus licheniformis RB16 isolated from cattle faeces - DILEK OZGUN EKIZ; UGUR COMLEKCIOGLU; NAZAN COMLEKCIOGLU; ASHABIL AYGAN (Anais da Academia Brasileira de Ciências)
Abstract Lichenan, 1,3-1,4-β-Glucan, a linear polysaccharide exists in the cell walls of various cereals, has garnered attention for its industrial applications due to its enzymatic breakdown by lichenase enzymes. In this study, Bacillus licheniformis strain RB16, isolated from cattle faeces, was identified as a robust lichenase producer. The lichenase gene, licA, was successfully cloned and characterized. The cloned RB16 lichenase (LicA) demonstrated its highest activity level at pH 7.5. It also retained over 50% of its activity within the pH range of 6.0–8.5 but experienced a decline to 40% at pH 9.0. LicA was active at temperatures ranging from 25 to 65 °C with an optimum at 45 °C. LicA exhibited more than 60% of its activity at the temperature range of 35–55 °C. Zymogram analysis confirmed LicA’s lichenan-degrading ability and structural analysis revealed a stable enzyme structure primarily composed of random coils and extended strands. Although LicA exhibited low thermostability, consistent with its relatively low α-helix content, it demonstrated promising industrial potential. Evolutionary analysis placed LicA within a cluster of closely related Bacillus lichenases, particularly B. halotolerans, B. atrophaeus, and B. spizizenii. These findings expand our understanding of lichenases of Bacillus and underscore its potential for various industrial applications.